Organic thin film transistor integration : a hybrid approach - Li, F. M. (Flora M.) (Wiley-VCH Verlag, 2011)
Research on organic electronics (or plastic electronics) is driven by the need to create systems that are lightweight, unbreakable, and mechanically flexible. With the remarkable improvement in the performance of organic semiconductor materials during the past few decades, organic electronics appeal to innovative, practical, and broad-impact applications requiring large-area coverage, mechanical flexibility, low-temperature processing, and low cost. Thus, organic electronics appeal to a broad range of electronic devices and products including transistors, diodes, sensors, solar cells, lighting.